2022
DOI: 10.3390/w14050693
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical Processes and Potential Exposure Risk of Arsenic-Rich Groundwater from Huaihe River Plain, China

Abstract: Arsenic poses a danger to environmental health, and arsenic-rich groundwater is a key exposure risk for humans. The distribution, migration, and enrichment of arsenic in groundwater is an important environmental and public health problem. Currently, the Huaihe River Basin is identified as a region of arsenic-rich groundwater in China. This study aims to assess arsenic-rich groundwater potential pollution risk, analyze the hydrogeochemical processes, and trace the ion source based on an analysis of groundwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Therefore, it can be concluded that the broad range of human activities influence the pollution concentrations in SW resources. A comprehensive study was conducted to explore the population under arsenic risk, which showed that highly populated areas in China with a greater percentage of inhabitants are affected by arsenic toxicity (Xu et al, 2022).…”
Section: High Equal Frequency Factors In Water Bodiesmentioning
confidence: 99%
“…Therefore, it can be concluded that the broad range of human activities influence the pollution concentrations in SW resources. A comprehensive study was conducted to explore the population under arsenic risk, which showed that highly populated areas in China with a greater percentage of inhabitants are affected by arsenic toxicity (Xu et al, 2022).…”
Section: High Equal Frequency Factors In Water Bodiesmentioning
confidence: 99%
“…The formation of arsenic-bearing groundwater is the result of a series of water-rock interactions, hydrogeochemistry and geological microorganisms. The release mechanisms are mainly as follows: desorption, reductive dissolution of arsenic-bearing minerals, oxidation of arsenic-bearing minerals and the direct reduction of arsenic [17][18][19][20][21][22]. There are mainly two forms of arsenic in nature, inorganic arsenic and organic arsenic, and its main valence states are As 3+ and As 5+ .…”
Section: Introductionmentioning
confidence: 99%
“…In China, more than 19 million people are exposed to arsenic-rich water (Xu et al, 2022). Thus, it is urgent to remediate the arsenic-contaminated water by effective methods.…”
Section: Introductionmentioning
confidence: 99%